ANALISIS PENGARUH DISIPLIN, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT METRO INTI PURNAMA - Rahman, Aditya Nur; Silalahi, Amat Pintu Batu; Wihara, Dhiyan Septa (Universitas Nusantara PGRI Kediri, 2021)
The problems in this research are : (1) Do the variabbles dicipline, work environment and compensation have partial effect to employee performance. (2) Do the variables dicipline, work environment and compensation have simultaneous effect on employee performance.Collection techniques in this research using questionnaire. Wiht independent variables dicipline, work environment, and compensation, while dependent variables is employee performance. The approach used in research is quantitative approach. In this research the population is 55 employees and sample is 35 employees, analysis techniques used in this research include desciptive analysis,validity test, reliability test, classical assumption test, multiple linear analysis, t test and F test. Conclusions in this research that partiaily (t test)shows dicipline (x1), work environment(x2),compensations (x3) which have significant influence employee performance (Y). simultaneously (F test) shows independent variables (dicipline, work environment, and compensation) have significant effect to employee performance. Keywords:dicipline, work environment, compensation